Uji Daya Simpan Sambal Kecicang dengan Penyimpanan Vakum - Martha Lisa Br Tarigan; Ni Made Suriani; Risa Panti Ariani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the organoleptic storage life of kecicang chili sauce using vacuum storage. The research design is experimental, involving 3 trained panelists, all of whom are lecturers from the Culinary Arts Vocational Education Study Program. The data collection method used in this study was observation through organoleptic testing using a 5-point Likert scale, namely 5) Very Good, 4) Good, 3) Fairly Good, 2) Not Very Good, 1) Very Poor. Data analysis used quantitative descriptive methods. The results of this study indicate that: 1) Processing affects the quality of kecicang chili sauce, using a technique that involves grinding the ingredients using a chopper, cooking at a temperature of ±70°C, and then vacuum packing. The organoleptic test results showed that vacuum storage was able to maintain the sensory properties of the sambal, as assessed from the aspects of colour, distinctive kecicang aroma, kecicang texture, solid dough texture, and distinctive kecicang taste, which were rated “fairly good” based on colour, aroma, texture, and taste. Vacuum-sealed sambal maintained its best quality until day 3rd, with no signs of leaking. The most significant changes occurred in the flavor and aroma, rendering it unfit for consumption. The sambal packaging, which showed no signs of leaking, maintained its sensory quality until day 5.